REPRESENTATION AND RESISTANCE AGAINST THE PATRIARCHAL SYSTEM IN THE DIGITAL LITERATURE ERA: THE FILM BIG EYES - Pratiwi, Dyani Prades; Hawa, Andina Meutia; Nesa, Fakhria (Jurnal Kata : Bahasa, Sastra, dan Pembelajarannya, 2023)
The patriarchal system is one of the problems in gender studies that is still described in the era of digital literature. Digital literature has a dynamic characteristic, which makes film categorized as a literary work by focusing on the story narrative. One of the films that contains the issue of patriarchy is Tim Burton's Big Eyes. This study aims to describe the patriarchal structure in digital literature using a qualitative descriptive method and Silvia Walby's feminist approach. The results of the research show that the six structures of the patriarchal system are related to each other but are centered on one main structure, Culture. As a digital literary work, the film Big Eyes also represents the resistance of the main female character, which can illustrate how the feminist movement is and how women should be able to fight against all forms of oppression caused by the patriarchal system.  Sistem patriarki menjadi salah satu permasalahan dalam kajian gender yang masih tergambar di era sastra digital. Sastra digital mempunyai sifat dinamis yang menjadikan film dikategorikan sebagai karya sastra dengan menitik beratkan pada narasi cerita. Salah satu film yang memuat isu patriarki adalah Big Eyes karya Tim Burton. Penelitian ini bertujuan untuk mendeskripsikan struktur patriarki dalam sastra digital dengan menggunakan metode deskriptif kualitatif dan pendekatan feminis Silvia Walby. Hasil penelitian menunjukkan bahwa keenam struktur sistem patriarki saling berkaitan satu sama lain namun berpusat pada satu struktur utama yaitu Kebudayaan (Culture). Sebagai sebuah karya sastra digital, film Big Eyes juga merepresentasikan perlawanan dari tokoh utama perempuan, yang dapat menggambarkan bagaimana gerakan feminisme dan bagaimana perempuan harus mampu melawan segala bentuk penindasan yang diakibatkan oleh sistem patriarki.